‘Colonising the Future’: Migrant Crossings on the English Channel and the Discourse of Risk - Emma Jacobs (Janeway JS, 2020)
In November of 2018, a small number of Middle Eastern migrants began crossing the English Channel to Dover in dinghies and fishing boats—a mode of crossing that had previously been somewhat rare. Despite the relatively low numbers, state and media responses to these events have been widespread and often alarmist, with the discourse of ‘risk’ becoming particularly prevalent. This paper explores the representational politics of this coverage, focusing primarily on online media from BBC News and press statements from the UK Home Office. Through a close reading of these texts, I argue that the language of risk serves to inscribe (ir)responsibility onto the bodies of migrants, presenting them as threats in need of management who are putting themselves and others at risk through their recklessness. Obscured from the discourse is the deeper causality of this risk—the fact that the same state actors who portray the migrants as unnecessary risk-takers are in many ways responsible for the conditions of ‘deterrence’ that make the risky option the only way. This moralisation and monopolisation of risk is ultimately part of a larger ideological discourse that serves to colonise possible futures. By placing the discourse of risk in historical and political context, this paper seeks to draw out the nuanced ways in which ascriptions of risk and practices of risk-management contribute to the perpetuation of a (neo)colonial and capitalist world order, whose violent effects are enacted in this instance upon subaltern migrants.
Keywords: Murakami Haruki; Don DeLillo; object-oriented ontology; Realism; capitalism